DOCENTES NEGRAS DA UFMS E AS MODALIDADES DE IDENTIFICAÇÃO RACIALIZADA: DISCURSO E(M) RESISTÊNCIA - OVÍDIO DA CONCEIÇÃO BATISTA JÚNIOR (2024)
This research focuses on the emergence to racialize identification modalities when black female professors at UFMS produce narratives about themselves. To this end, I use the theoretical-methodological device of Pecheuxtian Discourse Analysis, in dialogue with Black Feminism. Methodologically based on a qualitative-interpretative approach, the description and interpretation of the DSs – Discursive Sequences (Courtine, 2009), extracted from the responses obtained through semi-structured interviews, occur in direct and constitutive relation with their conditions of production (Orlandi, 2005). Within the epistemological framework, I conjecture the following question: “How are the modalities of racialized identification constituted in the responses of self-declared black female professors, when they talk about their academic trajectories at UFMS?” Given this concern and adding it to the ontological questions of a researcher based on a subject position of masculinity – a black man – I establish, as a general objective, to analyze the processes of racialized identification of self-declared black female professors at UFMS, in the beat between the discourses of self and the gesture of interpretation (Orlandi, 2012) of the analyst. In line with the greater purpose, the specific objectives of the study are: a) to problematize how intersectionality intersects in the battle for racial democracy and the end of sexist and patriarchal oppression (Carneiro, 2003; Gonzalez, 2020; Kilomba, 2019) that affects the trajectory of insertion and performance of black female professors at UFMS; b) to outline, in light of an in-between discipline, the conditions of production and the research process within the scope of the debate on racialized discourses and the modalities of identification; c) exercise a discursive listening (Orlandi, 2005) of the SDs. In view of the objectives outlined, I propose the thesis that the discursive construct of racialization at UFMS emerges as an effect of the ideological interpellation (Pêcheux; Fuchs, 1997) of the subjects investigated who counter-identify (Pêcheux, 2009) with a social formation that, in the scope of this work, regulates a patriarchal and racist DF. In the beat (Freire, 2014) between the narratives of themselves (theirs) and another subject-position – that of the researcher – beyond trajectories marked by the prohibition of stabilized discourses on what it is to be a black professor in higher education and, concomitantly with the achievements narrated, there is, as a recurrence, the production of resistance (Pêcheux, 2014) to epistemicide (Carneiro, 2003). In the analyzed SDs, this occurs mainly in the articulation of two marks on the linguistic surface: the denial and the presentification of absence. Regarding the historicity with which the non-full identification with the knowledge defended by the subject-form that operates regulating a patriarchal and racist DF emerges, in the game between recognition and representation, the legitimacy of the occupied place can be a preponderant part in the production of more racialized epistemic sensibilities in the university environment. Keywords: Black female professors. Black masculinity. Racialized discourses. Higher education.